Juego simbólico y el lenguaje oral en niños de la institución educativa inicial N°62448 Las Amazonas, Yurimaguas 2024 - Tello Fatama, Magnolia Peruvia (2025)
The main objective of the present study was to determine the relationship between symbolic play and the development of oral language in the children of the Initial Educational Institution N°62448 Las Amazonas Yurimaguas, in the year 2024. For this, a basic type of research was carried out, with a quantitative approach and a non-experimental, correlational and transectional design. The sample was made up of 51 children. Data collection was carried out through the observation technique, using a structured guide, whose validity was guaranteed through the review and approval of a committee of experts in the educational area. The results obtained showed a significant relationship between symbolic play and oral language, with a Kendall's Tau-b coefficient of 0.755 and a significance of 0.000. This confirms that children who actively participate in symbolic games have better development in their oral language. In conclusion, symbolic play is positioned as a key tool in children's linguistic development, which highlights the importance of systematically incorporating it into pedagogical strategies both at school and at home.